Core-shell nanoparticles and method for producing same
By using core-shell nanoparticles as anode materials for Li-ion batteries, the problems of irreversible capacity loss, dendrite formation and short cycle life of graphite and silicon anodes are solved, achieving battery performance with high capacity, stability and long cycle life. .
Patent Information
- Application Number
- CN202380047041.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-14
- Filing Date
- 2023-04-14
- Publication Date
- 2025-01-24
AI Technical Summary
In existing Li ion batteries, graphite anode has irreversible capacity loss, dendrite formation and safety problems, while silicon anode has short cycle life due to expansion and contraction, making it difficult to replace graphite.
The nuclear shell nanoparticles are used as anode material. Among them, the nucleus part is NB and NBS2, and the shell part is NBSXoy · ZH2O. Under inert conditions, the sulfur vapor can be used to oxidize and hydrophilize the nuclear shell nanoparticles through NB metal nanoparticles.
A high -capacity and stable anode material can be achieved. It can provide an initial charging/discharge capacity greater than 1500mAh/g between 0.01V and 3.0V. The cycle stability reaches at least 300 cycles, and it can effectively reduce the impedance of the LI metal anode.
Smart Images

Figure CN119365252A_ABST
Abstract
Description
Technical Field
[0001] In general, the present invention relates to core-shell nanoparticles and composites for use as anodes in batteries. The present invention also relates to methods of making the same. Background Art
[0002] The market size of anode materials is above $50 billion as of 2021. Research into high-capacity anode materials for building energy-dense batteries has led to the use of silicon and Li metal. The energy density of automotive batteries using lithium nickel manganese cobalt oxide (NMC) and lithium nickel cobalt aluminum oxide (NCA) cathodes paired with silicon or Li metal dominant anodes is expected to increase by up to 50%, thereby reducing the $ / kWh cost by 30-40% in less than a decade. Most existing Li-ion batteries use conventional anode materials such as graphite (intercalation reaction), which is usually used as a mixture of natural and synthetic graphite. Graphite provides a specific capacity of 330mAh / g, but there are various problems such as dendrite formation and Li metal plating, which can lead to irreversible capacity loss and safety issues.
[0003] When alkali and alkaline earth metals (such as Li metal) are used as anodes, they undergo plating / stripping reactions, while cathodes undergo insertion / deinsertion reactions (as in the case of insertion compounds such as LiNiMnCoO2, LiMn2O4, LiCoO2, etc.) or conversion reactions, such as sulfur cathodes. Most solid-state and Li-S batteries use Li metal as anode, and therefore, most of the research and start-ups involve solving key issues associated with it, such as irreversible capacity loss, dendrite formation, anode-based battery impedance, stability, etc.
[0004] Unlike graphite, silicon does not use an intercalation mechanism to store lithium ions. Instead, it operates via a "conversion" mechanism, where silicon and lithium atoms form an electrochemical alloy that breaks and restores chemical bonds during the charge-discharge cycle. The name conversion comes from converting or transforming from one structure to another. The bonds formed in the conversion reaction are much stronger (the reason they can store more energy). However, these bonds are more difficult to form and break in a repeatable manner without long-term damage. Achieving silicon anode cycling capability is technically more challenging. Despite a long history of development (1953 to present), there are no high-capacity commercial Li-ion batteries where silicon anodes completely replace graphite. About 1% of the anode materials currently produced worldwide are silicon-based. Small amounts of silicon are used as additives in graphite-based batteries. The Panasonic / Tesla battery contains about 5% silicon in the form of silicon oxide blended with graphite. The main challenge with silicon is that it expands 300% when it reacts with lithium during the charging process, and contracts 300% during discharge. In contrast, graphite expands and contracts about 7% when charging and discharging. This swelling causes problems like particle crushing, solid electrolyte interface (SEI) damage, and side reactions that trap lithium, which prevents silicon from replacing graphite. Battery and battery material manufacturers mix 3-5% silicon into graphite to make anodes and overcome this challenge. This solution increases energy density by about 10-20%. Adding more silicon will significantly shorten the cycle life for any practical application.
[0005] Pure silicon anodes typically cannot achieve more than about 100 full charge-discharge cycles and cannot be replicated on a large scale in a cost-effective manner.
[0006] In view of the current development trend of electric vehicles, batteries with greater storage capacity, better charge-discharge cycles, battery life, and / or reduced weight are needed.
[0007] It would be desirable to overcome or ameliorate at least one of the above problems. Summary of the invention
[0008] The present invention provides a core-shell nanoparticle comprising:
[0009] a) a core comprising Nb and NbS2, preferably NbS2, and
[0010] b) a shell of formula (I):
[0011] Nb x O y ·zH2O(I)
[0012] in
[0013] x is a number from 0 to 5;
[0014] y is a number from 0 to 3; and
[0015] z is a number from 0 to 10.
[0016] In some embodiments, x, y, and z are integers.
[0017] In some embodiments, the core-shell nanoparticles have a particle size of about 10 nm to about 10,000 nm.
[0018] In some embodiments, the core-shell nanoparticles have a shell thickness of about 5 nm to about 900 nm.
[0019] In some embodiments, the core-shell nanoparticles are lithiated.
[0020] The present invention also provides a composite material, comprising:
[0021] a) a substrate; and
[0022] b) core-shell nanoparticles as disclosed herein in contact with a substrate;
[0023] The substrate is selected from graphite, graphene, alkali metal, alkaline earth metal or alloys thereof, and a current collector comprising carbon, metal, intermetallic alloy and alloy and optionally alkali metal and alkaline earth metal.
[0024] In some embodiments, the core-shell nanoparticles are dispersed within a substrate.
[0025] In some embodiments, the core-shell nanoparticles are formed as a coating on a substrate.
[0026] In some embodiments, the coating is characterized by a thickness of about 10 nm to about 500 μm.
[0027] In some embodiments, when the core-shell nanoparticles are formed as a coating on a substrate, the substrate is Li metal.
[0028] In some embodiments, when the core-shell nanoparticles are formed as a coating on a substrate, the substrate is carbon paper, and the coating is characterized by a ratio of core-shell nanoparticles:carbon black:binder of about 8:1:1.
[0029] In some embodiments, when the core-shell nanoparticles are formed as a coating on a substrate, the substrate is a Cu foil, and the coating is characterized by a ratio of core-shell nanoparticles:carbon black:binder of about 9:0.5:0.5.
[0030] In some embodiments, when the core-shell nanoparticles are formed as a coating on a substrate, the substrate is carbon paper, and the coating is characterized by a ratio of core-shell nanoparticles:graphene:carbon black:binder of about 2:6:1:1.
[0031] In some embodiments, the composite material is characterized by an electrical conductivity at least about 100 times that of Li metal.
[0032] The present invention also provides a battery comprising an anode, wherein the anode comprises the core-shell nanoparticles as disclosed herein.
[0033] In some embodiments, the battery is characterized by a minimum capacity of at least about 800 mAh / g over a voltage range of about 0.01 V to about 2.8 V.
[0034] In some embodiments, the battery is characterized by a stable specific capacity of about 1,000 mAh / g to about 5,000 mAh / g.
[0035] In some embodiments, the battery is characterized by a cycle discharge specific stability of at least 45 mAh / g after 20 cycles.
[0036] In some embodiments, the cell is characterized by a median voltage that is at most about 1 / 10 that of Li metal.
[0037] In some embodiments, the battery is characterized by a cycling stability of at least 300 cycles.
[0038] The present invention provides a method for synthesizing core-shell nanoparticles as disclosed herein, the method comprising:
[0039] a) passing sulfur vapor through Nb metal nanoparticles under inert conditions; and
[0040] b) oxidizing and hydrating the nanoparticles of step (a) to form core-shell nanoparticles.
[0041] In some embodiments, the inert condition is a constant flow of an inert gas.
[0042] In some embodiments, the inert gas is selected from argon, nitrogen, or a combination thereof.
[0043] In some embodiments, step (a) is performed at about 900°C to about 1200°C.
[0044] In some embodiments, step (b) is performed by exposing the nanoparticles of step (a) to air. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Embodiments of the invention will now be described by way of non-limiting examples with reference to the accompanying drawings, in which:
[0046] Figure 1 Shows NbS x O y ·XRD of zH2O nanoparticles (NbSx).
[0047] Figure 2 Shows the current charge-discharge behavior of NbSx coated on a) carbon paper as a current collector, E1 electrolyte; b) copper as a current collector, A1 electrolyte. The capacity is based only on the NbSx active material.
[0048] Figure 3 Shows the current charge-discharge behavior of the NbSx graphene composite coated on a carbon current collector using A1 electrolyte.
[0049] Figure 4 Shows the current charge-discharge behavior of NbSx coated on a copper current collector, which uses a carbon fiber spacer current collector between the A1 electrolyte and the Celgard 2325 separator and the anode.
[0050] Figure 5 Compares the current charge-discharge behavior of NbSx and NbSx graphene composite anode materials relative to NMC532 single crystal in a full cell configuration using A1 electrolyte.
[0051] Figure 6 Compares the rate, cycling performance, and Coulombic efficiency of commercial graphite, NbSx, and NbSx graphene composite anode materials relative to NMC532 single crystal in a full cell configuration using A1 electrolyte.
[0052] Figure 7 Compares the electrochemical impedance spectra of Li coated with NbSx, untreated Li (Li itself), and Li treated with Li3N as the working electrode with Li as the counter electrode and reference electrode using E1 electrolyte.
[0053] Figure 8 Compares the decrease in the median voltage during long-term cycling during current charge-discharge on cells containing Li coated with NbSx, untreated Li, and Li treated with Li3N as the working electrode with Li as the counter electrode and reference electrode. Detailed Description
[0054] The present invention is based on the understanding that NbS x O y ·zH2O nanoparticles (where 0 < x < 5, 0 < y < 3, 0 < z < 10) (hereinafter referred to as "NbSx" in this application) can play an important role in high-capacity (>1500 mAh / g) and stable anode materials and can be effectively and continuously produced on a large scale.
[0055] Without wishing to be bound by theory, the inventors evaluated Nb foil as a collector for the cathode in a Li-S battery. It exhibited an initial low capacity of about 200 mAh / g, and after 100+ cycles, the capacity unexpectedly increased to 450 mAh / g. Compared with any other Li-S battery configuration at the time, the battery provided a stable capacity at a higher rate and a longer cycle life (>500 cycles). This result convinced the inventors that the electrochemical charge / discharge process may have produced intermediate byproducts from niobium and sulfur. It is believed that the intermediate byproducts can be used to construct a conductive solid electrolyte interphase (SEI) layer on the Li metal anode, which improves the stability of the Li-S battery. Therefore, the inventors are committed to further developing and synthesizing NbSx materials through thermochemical reactions.
[0056] In some embodiments, when NbSx is used as an artificial SEI protective layer on Li metal, NbSx reduces the impedance of the Li metal anode to less than 1 / 100 compared to unprotected Li metal. Further studies of electrochemical performance revealed that this material provides reversible charge / discharge capacity, or exhibits redox behavior between 0.01 and 0.2V relative to Li. NbSx provides an initial charge / discharge capacity of greater than 1,500mAh / g between 0.01 and 3.0V, with most of the discharge / charge occurring between 0.01 and 0.4V, making it a potential anode material for alkali and alkaline earth metal / metal ion batteries (e.g., Li ion, Na ion, Al ion, Li metal, and Na metal batteries). When used as an anode in an existing Li ion battery, it can increase energy density by about 15-20% and improve safety by preventing dendrite formation. NbSx has the potential to surpass silicon anodes as an anode material with its higher capacity and stability.
[0057] Therefore, the present invention provides a core-shell nanoparticle comprising:
[0058] a) a core comprising Nb and preferably comprising NbS2; and
[0059] b) a shell of formula (I):
[0060] Nb x O y ·zH2O(I)
[0061] in
[0062] x is a number from 0 to 5;
[0063] y is a number from 0 to 3; and
[0064] z is a number from 0 to 10.
[0065] Core-shell nanoparticles can be used as electrochemically active materials in battery applications.
[0066] Since the electrochemical discharge / charge is close to 0V relative to Li, higher cell voltages and thus higher energy density can be achieved. High specific capacities (>1,500mAh / g) can also be achieved, which enables the development of electrodes with higher tap density, thus achieving high areal capacities (>4mAh / cm 2 ), producing batteries with higher energy density. NbSx materials can be synthesized using environmentally friendly materials, are less expensive (compared to Si), and avoid supply chain issues for raw materials.
[0067] NbSx materials can be used to provide high-performance and durable anodes to build batteries with high energy density and long life. It is expected that this technology will be easy to adopt and implement; battery manufacturing companies can use this anode to replace their existing anodes. Specifically, NbSx can be used as an active anode material and electrode formulation for alkali and alkaline earth ion / metal batteries (such as Li ion, Na ion, Li-S, Al ion, Na metal, Li metal, solid-state batteries, etc.). In a broader sense, NbSx can replace all existing anode materials (such as graphite and silicon) in the current Li ion market. NbSx can directly compete with other high-capacity anode materials such as silicon, silicon monoxide, and composites. NbSx can also be used as an anode for Na ion batteries, replacing the currently used low-capacity (~200mAh / g) hard carbon-based anode materials. This will make it possible to build a battery architecture for high energy density Na ion batteries. Lithiated NbSx anodes can also be combined with non-lithiated cathode materials (such as MnO2, NiO, FeS2, and CS) to build Li ion and Li-S batteries. NbSx can be used as an artificial solid electrolyte interface material for alkali metals (such as Li, Na, etc.) to improve the electrochemical performance of alkali metal batteries.
[0068] In some embodiments, x, y, and z are integers. In some embodiments, x is a number from 1 to 5, 2 to 5, 3 to 5, or 4 to 5. In some embodiments, y is a number from 1 to 3, or 2 to 3. In some embodiments, z is a number from 1 to 10, 2 to 10, 3 to 10, 4 to 10, 5 to 10, 6 to 10, 7 to 10, 8 to 10, or 9 to 10.
[0069] In some embodiments, x is a number from 1 to 5, and y is a number from 1 to 3. In some embodiments, x is a number from 2 to 5, and y is a number from 1 to 3. In some embodiments, x is a number from 3 to 5, and y is a number from 1 to 3. In some embodiments, x is a number from 4 to 5, and y is a number from 1 to 3. In some embodiments, x is a number from 1 to 5, and y is a number from 1 to 2. In some embodiments, x is a number from 1 to 5, and y is a number from 2 to 3.
[0070] Certain particle size range can be desirable to obtain suitable conductivity and ionic conductivity and structural stability. In some embodiments, the particle size of core-shell nanoparticles is from about 10nm to about 1000nm. In other embodiments, the particle size is from about 10nm to about 900nm, from about 10nm to about 800nm, from about 10nm to about 700nm, from about 10nm to about 600nm, from about 10nm to about 500nm, from about 10nm to about 400nm, from about 10nm to about 300nm, from about 10nm to about 200nm, from about 10nm to about 100nm, from about 10nm to about 80nm, from about 10nm to about 60nm or from about 10nm to about 40nm. In some embodiments, the particle size is from about 10nm to about 280nm, from about 10nm to about 260nm, from about 10nm to about 240nm, from about 10nm to about 220nm, from about 10nm to about 200nm or from about 40nm to about 200nm.
[0071] In some embodiments, the particle size of the core-shell nanoparticles is from about 10 nm to about 10000 nm. In some embodiments, the particle size of the core-shell nanoparticles is from about 10 nm to about 9000 nm, from about 10 nm to about 8000 nm, from about 10 nm to about 7000 nm, from about 10 nm to about 6000 nm, from about 10 nm to about 5000 nm, from about 10 nm to about 4000 nm, from about 10 nm to about 3000 nm, from about 10 nm to about 2000 nm, from about 20 nm to about 2000 nm, from about 30 nm to about 2000 nm, from about 40 nm to about 2000 nm, from about 50 nm to about 2000 nm, from about 70 nm to about 2000 nm, from about 100 nm to about 2000 nm, from about 200 nm to about 2000 nm, from about 300 nm to about 2000 nm, from about 400 nm to about 2000 nm, or from about 500 nm to about 2000 nm.
[0072] In some embodiments, the shell thickness of the core-shell nanoparticle is from about 5nm to about 900nm. In other embodiments, the shell thickness is from about 5nm to about 900nm, from about 5nm to about 800nm, from about 5nm to about 700nm, from about 5nm to about 600nm, from about 5nm to about 500nm, from about 5nm to about 400nm, from about 5nm to about 300nm, from about 5nm to about 200nm, from about 5nm to about 100nm, from about 5nm to about 80nm, from about 5nm to about 60nm, from about 5nm to about 40nm, from about 5nm to about 20nm, or from about 5nm to about 10nm.
[0073] In some embodiments, the core-shell nanoparticles are lithiated. In this regard, the core and / or shell of the core-shell nanoparticles are doped with lithium. Lithiation enables the material to be used as an anode for a relatively unlithiated cathode (such as MnO2, FeS2, CuF2, FeF3, etc.). The lithium present in the core-shell is active and participates in the electrochemical reaction.
[0074] In some embodiments, the core-shell nanoparticles have one Li per core-shell material formula unit. In some embodiments, the core-shell nanoparticles are characterized by a molar ratio of Li to core-shell nanoparticles of 1: 1. In other embodiments, the molar ratio is 1.1: 1, 1.2: 1, 1.3: 1, 1.4: 1 or 1.5: 1.
[0075] The present invention also provides a composite material, comprising:
[0076] a) a substrate; and
[0077] b) core-shell nanoparticles as disclosed herein in contact with a substrate.
[0078] The composite material can be used as an anode material.
[0079] In some embodiments, the substrate is selected from graphite, graphene, alkali metals, alkaline earth metals or alloys thereof, and current collectors including carbon, metals, intermetallic alloys and alloys and optionally alkali metals and alkaline earth metals. For example, the substrate can be Li metal.
[0080] The current collector may be a mesh, wire, foil / sheet (perforated or solid), foam or fiber. The current collector may be porous. The current collector may include a conductive metal, alloy, polymer or carbon.
[0081] In some embodiments, the core-shell nanoparticles are dispersed within a substrate.
[0082] The core-shell nanoparticles can be used as active materials for lithium-ion battery anodes, just like any other anode active materials (e.g., graphite) currently used by the industry. Alternatively, in some embodiments, the core-shell nanoparticles are formed as a coating on a substrate. In some embodiments, the coating is characterized by a thickness of about 10 nm to about 500 μm. In some embodiments, the thickness is about 20 nm to about 500 μm, about 40 nm to about 500 μm, about 60 nm to about 500 μm, about 80 nm to about 500 μm, about 100 nm to about 500 μm, about 200 nm to about 500 μm, about 400 nm to about 500 μm, about 600 nm to about 500 μm, about 800 nm to about 500 μm, about 1 μm to about 500 μm, about 5 μm to about 500 μm, about 10 μm to about 500 μm, about 50 μm to about 500 μm, about 100 μm to about 500 μm, or about 200 μm to about 500 μm. In some embodiments, the thickness is from about 5 μm to about 450 μm, from about 5 μm to about 400 μm, from about 5 μm to about 350 μm, from about 5 μm to about 300 μm, from about 5 μm to about 250 μm, from about 5 μm to about 200 μm, from about 5 μm to about 150 μm, from about 5 μm to about 100 μm, or from about 5 μm to about 50 μm. In some embodiments, the thickness is from about 200 μm to about 500 μm, from about 250 μm to about 500 μm, or from about 300 μm to about 500 μm.
[0083] In some embodiments, when the core-shell nanoparticles are formed as a coating on a substrate, the substrate is Li metal.
[0084] In some embodiments, the core-shell nanoparticles are provided to the substrate in the form of a slurry through a coating. Thus, the coating further comprises other components, such as a binder and carbon black.
[0085] In some embodiments, the weight ratio of core-shell nanoparticles in the slurry is about 20% relative to the slurry. In other embodiments, the weight ratio is about 25%, about 30%, about 35%, about 40%, about 45%, about 50%, about 55%, about 60%, about 65%, about 70%, about 75%, about 80%, about 85%, about 90% or about 95%. In other embodiments, the weight ratio is about 20% to about 95% relative to the slurry.
[0086] In some embodiments, the ratio of core-shell nanoparticles: carbon black is about 7:2 to about 9:0.5, or about 8:1 to about 9:0.5. In some embodiments, the ratio of core-shell nanoparticles to binder is about 7:2 to about 9:0.5, or about 8:1 to about 9:0.5.
[0087] In battery technology, there may be an adhesive to keep the coating particles together and help adhere the coating to the metal or separator. The adhesive also helps to form a film, helping to form a good particle dispersion in a solvent or water. The adhesive can also help the coating to be dispersed to provide a uniform slurry and discrete particles in the cathode and anode. The adhesive remains stable in the harsh environment of the battery where multiple reactions may occur. The adhesive can also have a certain degree of flexibility, so they will not break or produce defects. The adhesive can be based on organic solvents or based on water. Water-based adhesives can be but are not limited to PTFE, carboxymethyl cellulose, styrene butadiene rubber, natural adhesives (such as gum arabic or xanthan gum). Non-aqueous or organic solvent adhesives can be but are not limited to PVDF, PeOZ.
[0088] In some embodiments, when the core-shell nanoparticles are formed as a coating on a substrate, the coating is characterized by a ratio of core-shell nanoparticles:carbon black:binder of about 8:1:1, about 9:0.5:0.5, about 9.5:0.5:0, or about 6:3:1.
[0089] In some embodiments, when the core-shell nanoparticles are formed as a coating on a substrate, the substrate is carbon paper, and the coating is characterized by a ratio of core-shell nanoparticles:carbon black:binder of about 8:1:1.
[0090] In some embodiments, when the core-shell nanoparticles are formed as a coating on a substrate, the substrate is a Cu foil, and the coating is characterized by a ratio of core-shell nanoparticles:carbon black:binder of about 9:0.5:0.5.
[0091] The slurry may further include graphene. In some embodiments, the weight ratio of graphene in the slurry is about 60% relative to the slurry. In other embodiments, the weight ratio is about 50%, about 55%, about 65%, about 70%, about 75%, or about 80%. In other embodiments, the weight ratio is about 55% to about 80% relative to the slurry.
[0092] In some embodiments, when the core-shell nanoparticles are formed as a coating on a substrate, the substrate is carbon paper, and the coating is characterized by a ratio of core-shell nanoparticles:graphene:carbon black:binder of about 2:6:1:1.
[0093] Alternatively, dry electrode technology can be used without a slurry, for example, by using a hydraulic press to press the core-shell material and carbon directly onto carbon paper to obtain an anode ready for battery assembly.
[0094] In some embodiments, the composite material is characterized by a conductivity of at least about 100 times relative to Li metal. In other embodiments, the conductivity is at least about 90 times, about 80 times, about 70 times, about 60 times, about 50 times, about 40 times, about 30 times, about 20 times, or about 10 times.
[0095] The present invention also provides a battery comprising an anode, wherein the anode comprises the core-shell nanoparticles as disclosed herein.
[0096] In some embodiments, the battery is characterized by an initial specific capacity of at least about 1,000 mAh / g. In other embodiments, the specific capacity is from about 1,000 mAh / g to about 5,500 mAh / g. It is speculated that the unusually high capacity may be due to a more extensive conversion mechanism similar to silicon-based materials, which decays rapidly after the first few cycles, in contrast to the normal intercalation mechanism.
[0097] In some embodiments, the battery is characterized by a minimum capacity of at least about 800 mAh / g over a voltage range of about 0.01 V to about 2.8 V.
[0098] In some embodiments, the battery is characterized by a stable specific capacity of about 1,000 mAh / g to about 5,000 mAh / g. In other embodiments, the specific capacity is about 1,000 mAh / g to about 4,500 mAh / g, about 1,000 mAh / g to about 4,000 mAh / g, about 1,000 mAh / g to about 3,500 mAh / g, about 1,000 mAh / g to about 3,000 mAh / g, or about 1,000 mAh / g to about 2,500 mAh / g.
[0099] In some embodiments, the battery is characterized by a cycle discharge specific stability of at least 45 mAh / g after 20 cycles.
[0100] In some embodiments, the cell is characterized by a median voltage that is at most about 1 / 10 that of Li metal.
[0101] In some embodiments, the battery is characterized by a cycling stability of at least 300 cycles.
[0102] The present invention provides a method for synthesizing core-shell nanoparticles as disclosed herein, the method comprising:
[0103] a) passing sulfur vapor through Nb metal nanoparticles under inert conditions; and
[0104] b) oxidizing and hydrating the nanoparticles of step (a) to form core-shell nanoparticles.
[0105] In some embodiments, the inert condition is a constant flow of an inert gas.
[0106] In some embodiments, the inert gas is selected from argon, nitrogen, or a combination thereof.
[0107] In some embodiments, step (a) is performed at about 900°C to about 1200°C.
[0108] In some embodiments, step (b) is carried out by exposing the nanoparticles of step (a) to air. This step can be carried out at ambient temperature and humidity. Alternatively, the rate of oxidation and / or hydration can be controlled by controlling temperature and / or water vapor content. For example, the temperature can be from about 20°C to about 100°C, from about 30°C to about 100°C, from about 40°C to about 100°C, from about 50°C to about 100°C, from about 60°C to about 100°C, from about 70°C to about 100°C, from about 80°C to about 100°C, or from about 90°C to about 100°C. The humidity in the air can be from about 10% to about 99%, from about 10% to about 90%, from about 10% to about 80%, from about 10% to about 70%, from about 10% to about 60%, from about 10% to about 50%, from about 10% to about 40%, from about 10% to about 30%, or from about 10% to about 20%.
[0109] Example
[0110] Material Synthesis: The material is synthesized by passing sulfur vapor through niobium metal nanopowder. The niobium powder should preferably have the highest possible surface area to volume ratio. The Nb powder is in the form of nanometer-sized particles.
[0111] The synthesis is carried out in an inert atmosphere at a temperature between 1000 and 1100°C for 30 to 80 minutes under a constant gas flow (e.g. Ar). The synthesis is carried out in a furnace with a heating rate of 40°C / min or more. Argon is used as a carrier gas for the sulfur vapor. The reaction between niobium and sulfur occurs at the surface of the niobium nanoparticles. NbSx is treated in air (exposed to air) to oxidize and hydrate the material. Therefore, NbSx can contain oxygen and hydroxyl / water groups in its structure, so the molecular formula of NbSx can be written as: NbS x O y ·zH2O (where 0 <x<5,0<y<3,0<z<10)。
[0112] X-ray diffraction was performed at room temperature under ambient conditions using a Rigaku 6th generation MiniFlex Benchtop XRD system. Figure 1 Powder X-ray diffraction (XRD) of NbSx is shown.
[0113] In addition, NbSx can be lithiated electrochemically or via a thermochemical route to obtain a lithiated version of NbSx for use as an anode with relatively non-lithiated cathode materials such as MnO2, FeS2, and S.
[0114] NbSx can also be used in the following ways:
[0115] a) Directly as active material
[0116] b) Added as a composite additive to graphite or graphene to increase capacity
[0117] c) As protective coatings on alkali metals and alkaline earth metals or alloys or current collectors.
[0118] Construction of anodes with NbSx coatings
[0119] • The anode consists of NbSx coated on a current collector which is adsorbed / implanted / diffused with / consisting of carbon, metals, intermetallic alloys and alloys and optionally alkali and alkaline earth metals.
[0120] • The current collector can be in the form of mesh, wire, foil / sheet (perforated or solid), foam, fiber, with or without pores, and made of conductive metals, alloys, polymers or carbon structures.
[0121] The thickness of NbSx coating ranges from 5μm to 200μm, depending on the electrode design requirements.
[0122] NbSx acts as an artificial SEI protective layer, which also serves as a catalytic site to promote the nucleation / deposition of lithium while preventing particle pulverization over long-term cycling.
[0123] Anodes containing alkali metals and alkaline earth metals
[0124] a. In this type of anode, the current collector is embedded in alkali metals and alkaline earth metals or alloys.
[0125] b. NbSx is coated on alkali and alkaline earth metals or alloys, for example, by drop casting / tape casting, which acts as Li nucleation / deposition sites to form a stable SEI that supports rapid plating and stripping of alkali and alkaline earth metals.
[0126] c. Such anodes can be relatively electroactive materials (such as S, C, LiMn2O4 and Na2V6O 16 ) is used, the electroactive material containing or not containing an alkali metal or an alkaline earth metal in its composition.
[0127] Anodes free of alkali metals and alkaline earth metals
[0128] a. In this type of anode, the current collector does not contain any alkali metal and alkaline earth metal or alloy.
[0129] b. NbSx is directly coated on the current collector by drop casting / tape casting. The coated NbSx acts as a nucleation / conversion site for alkali metals and alkaline earth metals to form a stable SEI.
[0130] c. When such an anode is used in an electrochemical cell relative to an alkali metal or alkaline earth metal-containing cathode (such as nickel manganese cobalt (NMC), LiMn2O4 and LiFePO4), the alkali metal or alkaline earth metal ions undergo a conversion reaction with NbSx, and NbSx is adsorbed / injected / diffused onto / into the current collector. Thus, a stable SEI layer is formed, which further allows the plating / stripping of a thicker alkali metal or alkaline earth metal layer, thereby forming an anode in situ.
[0131] NbSx can be used as an active material for anodes, or as an additive in composites containing existing anode active materials to increase capacity, or as an artificial solid electrolyte interface protective coating for alkali metals and alkaline earth metals used as anodes in batteries.
[0132] NbSx in Batteries: NbSx as Active Material and / or Composite Additive for Anodes
[0133] Electrochemical characterization was performed using the synthesized NbSx. Current charging and discharging were performed to obtain the specific capacity of NbSx and to evaluate the rate and cycle life performance.
[0134] The working electrode or anode is manufactured in the following two configurations:
[0135] Anode configuration
[0136] Coating of a slurry containing NbSx, carbon black and binder in the following ratios:
[0137] 1) 8:1:1 on carbon paper (Avcarb P50)
[0138] 2) On Cu foil: 9:0.5:0.5
[0139] The electrodes were dried at 50°C overnight.
[0140] NMC532 cathode was prepared by casting a water-based slurry containing NMC532 single crystals, carbon black, binder in a ratio of 8:1:1 on carbon paper (Avcarb P50).
[0141] The cells were tested using two electrolyte systems, one based on a carbonate solvent and the other based on an ether solvent, named A1 and E1.
[0142] A1 electrolyte: 1M LiPF6 dissolved in carbonate solvent.
[0143] E1 electrolyte: 1 M LiTFSI dissolved in ether solvent.
[0144] Cell Architecture: All coin cells were made using standard CR2032 coin cell components made of stainless steel. Celgard 2325 separators made of polypropylene and 40 ul of electrolyte were used for all experiments.
[0145] · Half-cell: The half-cell was constructed by using Li metal chip as counter electrode and reference electrode relative to the working electrode. The working electrodes used here were NbSx coated on carbon and copper and NbSx graphene composite coated on carbon paper.
[0146] Full cells: Full cells were constructed by using NMC532 cathodes relative to graphite, NbSx, and NbSx graphene composite anodes, using A1 electrolyte.
[0147] Electrochemical performance analysis of NbSx:
[0148] 1) NbSx as the active material of anode:
[0149] As from Figure 2 As can be seen from the charge-discharge graph shown in a (current charge-discharge behavior), when NbSx was used as the active material coated on carbon paper, it provided >2,000 mAh / g and >6 mAh / cm in E1 electrolyte. 2 Specific capacity. Capacity is based on NbSx active material only. Figure 2 b shows the current charge-discharge performance of NbSx coated on a copper current collector, which provides an initial specific discharge capacity of 1,050 mAh / g and a first cycle specific capacity of 850 mAh / g in A1 electrolyte. The higher capacity of NbSx in ether-based solvents compared to carbonate-based solvents is due to the higher stability of the intermediate conversion products of NbSx in ether solvents.
[0150] However, NbSx in pure form can provide a minimum capacity of more than 800 mAh / g in the voltage range of 0.01 V to 2.8 V in both ether-based and carbonate-based electrolytes, which is higher than commercial graphite and comparable to silicon in terms of stability and areal capacity.
[0151] 2) NbSx composites improve capacity:
[0152] The composite of NbSx and graphene was prepared by ultrasonic treatment in a weight ratio of 1:3 and then dried in a vacuum oven to obtain the composite powder. The anode was fabricated by casting a slurry containing NbSx / graphene composite, carbon black, binder in a ratio of 8:1:1 on carbon paper (Avcarb P50).
[0153] The current charge-discharge performance of the NbSx / graphene composite was first evaluated in a half-cell configuration and then tested in a full-cell configuration. The NbSx / graphene composite provided an initial specific capacity of 1,899 mAh / g and a stable specific capacity of 1,000 mAh / g after 5 cycles. Figure 3 Shown is the current charge-discharge behavior of the NbSx graphene composite coated on a carbon current collector using an A1 electrolyte. The specific capacity is based on the total weight of the composite NbSx and graphene.
[0154] When carbon fiber is used as a spacer between the working electrode and the separator, it improves the stability and capacity retention of NbSx. In this cell configuration, the NbSx anode prepared as described in Anode Configuration 2 exhibits an initial specific capacity of 5,187 mAh / g and a stable specific capacity of >3,000 mAh / g after the first cycle. Figure 4 Shown is the current charge-discharge behavior of NbSx coated on a copper current collector using an Al electrolyte with a Celgard 2325 separator and a carbon fiber separator between the anode. The specific capacity is based on the weight of the NbSx active material.
[0155] Therefore, using carbon nanoobjects as additives or composited with NbSx can improve the stability and capacity of anode materials.
[0156] In addition, full-cell studies were performed to compare the rate, cycle life, and Coulombic efficiency of NbSx, NbSx / graphene composite, and graphite relative to NMC532 as the cathode. Figure 5 The current charge-discharge behavior of NbSx and NbSx-graphene composite anode materials using A1 electrolyte is shown. NbSx exhibits a higher nominal voltage and similar capacity. Therefore, NbSx has a higher energy density than the NbSx / graphene composite. On the other hand, the NbSx / graphene composite exhibits better rate performance, coulombic efficiency, and cycling stability than NbSx and commercial graphite. Figure 6 Comparison of rate, cycling performance, and coulombic efficiency of commercial graphite, NbSx, and NbSx graphene composite anode materials relative to NMC532 single crystal in a full cell configuration using A1 electrolyte is shown. Capacity is based on the combined weight of cathode and anode active materials.
[0157] NbSx as an artificial protective SEI layer
[0158] Typically, the Li metal anode (such as that used in Li-S and most solid-state batteries) has a Li excess of about 500%. This is to ensure that during the charge-discharge process, there is always a fresh layer of lithium on which the stripped lithium can plate itself. Excess lithium increases the cost and reduces the energy density of the battery, which defeats the purpose of using a high-capacity anode. Bare Li suffers from huge volume changes during repeated electroplating and stripping, during which a stable solid electrolyte interface (SEI) may not be formed on the surface. Continuous exposure of Li metal to the electrolyte causes the formation of insulating products and the consumption of electrolyte, resulting in low Coulombic efficiency and poor cycling performance. Modified electrolytes have been proposed to regulate the electrolyte / electrode interface and induce a rigid SEI during lithium plating. Many studies have revealed that active electrolyte components are continuously consumed during cycling, and therefore raise concerns about the life of practical Li metal batteries using modified electrolytes. Carbon materials and polymers are usually used to construct physical layers to prevent the penetration of dendrites in the Li anode (which reduces the plating and stripping efficiency on Li metal), thereby creating a Li isolation zone on the anode.
[0159] An ideal artificial SEI layer should actively bind to the electroplated Li to regulate the deposition behavior while maintaining its integrity upon long-term cycling.
[0160] We address the above issues in a different way by providing catalytic and conductive sites on NbSx for the plating and stripping of alkali and alkaline earth metals.
[0161] The synthesized NbSx was characterized using current charge-discharge and electrochemical impedance spectroscopy. Current charge-discharge was also performed to evaluate NbSx as a protective coating for Li metal by the drop in median voltage over long-term cycling.
[0162] The working electrodes were tested and their electrochemical performances were compared:
[0163] 1) Artificial protective SEI layer of NbSx on Li metal
[0164] 2) Artificial protective SEI layer of Li3N on Li metal
[0165] 3) Li metal as received (no coating)
[0166] The NbSx artificial protective SEI layer on Li metal was coated by drop casting NbSx and NMP in a ratio (w:v) of 15:100 on a Li metal chip with a diameter of 16 mm. The Li metal chip was purchased from MTI. The coated Li metal was thoroughly dried before use.
[0167] The cells were tested using E1 electrolyte.
[0168] Cell Architecture: All coin cells were made using standard CR2032 coin cell components made of stainless steel, Celgard 2325 separator, and 40ul electrolyte. Half cells were constructed using Li metal chips as counter and reference electrodes relative to the working electrodes described above.
[0169] Electrochemical analysis of NbSx as a protective coating:
[0170] Figure 7 Electrochemical impedance spectra of NbSx-coated Li, uncoated Li (Li itself), and Li3N-coated Li as working electrodes with Li as counter and reference electrodes are shown. Comparison of the electrochemical impedance spectra of different working electrodes shows that the conductivity of NbSx-coated Li is 25 times and >100 times that of Li3N-coated Li and commercial Li metal chips, respectively.
[0171] Furthermore, to evaluate and compare the long-term cycling stability between the working electrodes, more than 300 cycles of current charge-discharge were performed. Figure 8 The median voltage after long-term cycling is shown during current charge and discharge with NbSx-coated Li, uncoated Li, and Li3N-coated Li as working electrodes relative to Li as counter and reference electrodes. NbSx-coated Li shows higher stability over long-term cycling with a median voltage of about 1 / 10, indicating that NbSx-treated Li has high conductivity compared to the other two working electrodes. Therefore, it is demonstrated that NbSx creates a better artificial protective SEI layer for Li metal.
[0172] It will be appreciated that various aspects of the described embodiments are susceptible to numerous further modifications and permutations. Accordingly, the described aspects are intended to embrace all such changes, modifications and variations that fall within the spirit and scope of the appended claims.
[0173] Throughout this specification and the appended claims, unless the context requires otherwise, the word "comprise" and variations such as "comprises" and "comprising" will be understood to imply the inclusion of a stated integer or step or groups of integers or steps but not the exclusion of any other integer or step or groups of integers or steps.
[0174] Throughout this specification and the appended claims, unless the context requires otherwise, the phrase "consisting essentially of" and variations (such as "consists essentially of") should be understood to indicate that the listed elements are essential (i.e., necessary) elements of the invention. The phrase allows for the presence of other unlisted elements that do not materially affect the characteristics of the invention, but excludes other unspecified elements that affect the basic and novel characteristics of the defined method.
[0175] Reference in this specification to any previous publication (or information obtained therefrom) or any known matter is not and should not be regarded as an admission or recognition or any form of implication that the previous publication (or information obtained therefrom) or known matter constitutes part of the common general knowledge in the field of work involved in this specification.
Claims
1. A core-shell nanoparticle comprising: a) a core comprising Nb and preferably comprising NbS2; as well as b) a shell of formula (I): NbS x O y ·zH2O(I) in x is a number from 0 to 5; y is a number from 0 to 3; and z is a number from 0 to 10.
2. The core-shell nanoparticle of claim 1, wherein x, y and z are integers. 3 . The core-shell nanoparticle according to claim 1 , wherein the particle size of the core-shell nanoparticle is from about 10 nm to about 10000 nm. 4 . The core-shell nanoparticle according to claim 1 , wherein the shell thickness of the core-shell nanoparticle is from about 5 nm to about 900 nm. 5 . The core-shell nanoparticle according to claim 1 , wherein the core-shell nanoparticle is lithiated.
6. A composite material comprising: a) substrate; and b) core-shell nanoparticles according to any one of claims 1 to 5 in contact with the substrate; The substrate is selected from graphite, graphene, alkali metals, alkaline earth metals or alloys thereof, and current collectors comprising carbon, metals, intermetallic alloys and alloys and optionally alkali metals and alkaline earth metals. The composite material of claim 6 , wherein the core-shell nanoparticles are dispersed within the matrix.
8. The composite material of claim 6, wherein the core-shell nanoparticles are formed as a coating on the substrate.
9. The composite material of claim 8, wherein the coating is characterized by a thickness of about 10 nm to about 500 μm. 10 . The composite material according to claim 8 , wherein when the core-shell nanoparticles are formed as a coating on the substrate, the substrate is Li metal.
11. The composite material of claim 8 or 9, wherein when the core-shell nanoparticles are formed as a coating on the substrate, the substrate is carbon paper, and the coating is characterized by a ratio of the core-shell nanoparticles:carbon black:binder of about 8:1:
1.
12. The composite material of claim 8 or 9, wherein when the core-shell nanoparticles are formed as a coating on the substrate, the substrate is a Cu foil, and the coating is characterized in that the ratio of the core-shell nanoparticles: carbon black: binder is about 9:0.5:0.
5.
13. The composite material of claim 8 or 9, wherein when the core-shell nanoparticles are formed as a coating on the substrate, the substrate is carbon paper, and the coating is characterized in that the ratio of the core-shell nanoparticles:graphene:carbon black:binder is about 2:6:1:
1.
14. The composite material of any one of claims 7 to 13, wherein the composite material is characterized by an electrical conductivity at least about 100 times that of Li metal.
15. A battery comprising an anode, wherein the anode comprises the core-shell nanoparticles according to any one of claims 1 to 5.
16. The battery of claim 15, wherein the battery is characterized by a minimum capacity of at least about 800 mAh / g over a voltage range of about 0.01 V to about 2.8 V.
17. The battery of claim 15 or 16, wherein the battery is characterized by a stable specific capacity of about 1,000 mAh / g to about 5,000 mAh / g.
18. The battery of any one of claims 15 to 17, wherein the battery is characterized by a cycle discharge specific stability of at least 45 mAh / g after 20 cycles.
19. The battery of any one of claims 15 to 18, wherein the battery is characterized by a median voltage that is at most about 1 / 10 that of Li metal.
20. The battery of any one of claims 15 to 19, wherein the battery is characterized by a cycling stability of at least 300 cycles.
21. A method for synthesizing core-shell nanoparticles according to any one of claims 1 to 5, the method comprising: a) passing sulfur vapor through Nb metal nanoparticles under inert conditions; and b) oxidizing and hydrating the nanoparticles of step (a) to form the core-shell nanoparticles.
22. The method of claim 21, wherein the inert condition is a constant flow of an inert gas.
23. The method of claim 22, wherein the inert gas is selected from argon, nitrogen, or a combination thereof.
24. The method of any one of claims 21 to 23, wherein step (a) is performed at about 900°C to about 1200°C.
25. The method according to any one of claims 21 to 24, wherein step (b) is performed by exposing the nanoparticles of step (a) to air.